POTENSI PARIWISATA DALAM PEREKONOMIAN INDONESIA - Agung Nurmansyah (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2014)
The tourism sector has contributed 11 percent of the gross domestic product absorbing world with about 200 million workers. Or have an indirect impact of 800 million people.In 2012, the direct and indirect contribution to Indonesia's gross domestic product by 12 percent. Tourism potential is huge but much hampered infrastructure, security,promotion, and government policy. In addition to having a positive impact on the Indonesian economy. Tourism also has a negative impact on the economic and socialaspects, although still much more positive impact than negative impact.